Solution for packet reordering in manet’s using cross layer based routing protocol - Praveen Kumar Rao, K; T. Senthil Murugan, Dr (International Journal of Engineering and Technology, 2018)
TCP allows sharing the information about network status using Cross Layer mechanism for the different layers. The Cross Layer approach in wireless MANETs is provided for improving TCP performance. The Optimal Path or Route Selection is an important aspect for increasing energy efficiency and lifetime of the network. A proposal for Trust Aware Routing protocol is described for selecting an optimal route in MANETs. Direct and Indirect trust values are used for estimating the trust value of every node in the network. The route cost amount is estimated and the best path with minimum cost value is chosen for the network. The data packet is transmitted on the optimal path, and the optimal path is selected on the minimum cost value of the network. There is a possibility of the packets being dropped due to congestion and / or mobility and there are chances of the packets being reordered during the transmission process. Reorder Identification mechanism is the procedure used for dropped and / or reordered packets. The simulation results of the proposed work are compared with the existing work and it shows more effective in terms of energy efficiency and network lifetime.Â